The Effect of Cloud-Based Accounting Information Systems and Internal Control on The Quality of Financial Reports at PT Capella Dinamik Nusantara: Pengaruh Penggunaan Sistem Informasi Akuntansi Berbasis Cloud dan Pengendalian Internal Terhadap Kualitas Laporan Keuangan di PT Capella Dinamik Nusantara - Defina Elizabeth Yennata; Putri Wahyuni (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This study aims to analyze the relationship between cloud-based accounting information systems and internal control on the quality of financial statements at PT Capella Dinamik Nusantara. A quantitative approach was employed in the data collection process. The research population comprised 207 employees of PT Capella Dinamik Nusantara. Using purposive sampling, the final sample was reduced to 70 employees who met the specified criteria. Data were collected through the distribution of questionnaires using a Likert scale, followed by descriptive statistical analysis, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The regression equation obtained was: Financial statement quality = 11.060 + 0.739 cloud-based accounting information systems + 0.593 internal control + e. The t-test results revealed that the accounting information system variable significantly influenced financial statement quality at PT Capella Dinamik Nusantara (t = 76.478 > t-table 1.995). The internal control variable also significantly influenced financial statement quality (t = 4.275 > t-table 1.995). Furthermore, the F-test showed that both cloud-based accounting information systems and internal control simultaneously influenced financial statement quality (F = 48.703 > F-table 3.13). The coefficient of determination (R²) test indicated that 59.2% of the variation in financial statement quality was explained by cloud-based accounting information systems and internal control, while the remaining 40.8% was influenced by other factors outside the scope of this study.